2011
DOI: 10.1111/j.1442-1984.2011.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic selection on flowering phenology and size in two dioecious plant species with different pollen vectors

Abstract: Dioecious plants may be pollinated biotically by animals or abiotically via wind or water currents. It has been hypothesized that these two types of pollen vectors might impose contrasting selective pressures on plant flowering phenology. In the present study we describe the flowering phenology of two sympatric dioecious species with contrasting pollination modes: Mercurialis perennis (wind-pollinated) and Tamus communis (insectpollinated). We estimated selection differentials and gradients for flowering time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 56 publications
3
30
0
Order By: Relevance
“…Furthermore, insect pollinators responded to increased male attractiveness by visiting males more frequently than females. Our results coincide with studies in sexually dimorphic species that have shown allocation to attractive structures beneficing male function more than female function (Conner et al 1996;Vaughton and Ramsey 1998;Munguia-Rosas et al 2011).…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, insect pollinators responded to increased male attractiveness by visiting males more frequently than females. Our results coincide with studies in sexually dimorphic species that have shown allocation to attractive structures beneficing male function more than female function (Conner et al 1996;Vaughton and Ramsey 1998;Munguia-Rosas et al 2011).…”
Section: Discussionsupporting
confidence: 80%
“…With respect to the difference in the number of flowers between female and male individuals, in dioecious species it is common for male plants to produce more flowers per individual than female plants (Bram & Quinn 2000, Espírito-Santo et al 2003, Munguia-Rosas et al 2011, Barrett & Hough 2012. Male plants allocate more resources to produce more flowers because their fitness is directly linked to the number of pollen grains released.…”
Section: Discussionmentioning
confidence: 99%
“…Among these factors, size of individual plants has been found to influence their flowering phenology (Schmitt ; Dieringer ; Ollerton and Lack ; Torimaru and Tomaru ; Munguía‐Rosas et al. a), and probably its reproductive performance as well, mediating the attraction of animal vectors dispersing the pollen (Klinkhamer et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…The focus has been on species or population mechanisms and despite variation in flowering phenology among individuals within a population has been well documented, few studies have analyzed the factors affecting it (Primack 1980;Dieringer 1991;Ollerton and Lack 1998). Among these factors, size of individual plants has been found to influence their flowering phenology (Schmitt 1983;Dieringer 1991;Ollerton and Lack 1998;Torimaru and Tomaru 2006;Mungu ıa-Rosas et al 2011a), and probably its reproductive performance as well, mediating the attraction of animal vectors dispersing the pollen (Klinkhamer et al 1989). Plant size can influence the acquisition of resources, especially in forest ecosystems where light incidence decreases considerably from canopy to understory strata.…”
Section: Introductionmentioning
confidence: 99%